“Sports Maternalism”, to Train and Take Care: Ethnographic Investigation in Baton Twirling Clubs - Ly, Shia Manh (Frontiers in Sports and Active Living, 2021)
This article is the result of an ethnographic work on baton twirling clubs in Switzerland: clubs with few members coming from a modest origin, offering a social and physical activity of low legitimacy, composed of children and young girls. The supervision is mainly the responsibility of close volunteers: family members, friends or neighbors and, for the majority of them, women. It is therefore an environment where people know each other, where gestures of familiarity are the rule and where tensions may sometimes arise due to various conflicts of proximity. Baton twirling is based on a public display of participants and the competitive aspiration for a self-presentation that solicits feminine stereotypes. It shows sociabilities and socialities framed by gender and age relationships: within clubs, knowledge transmission and childcare are combined in women's practices. The relationships between women and children transcend learning relationships. These relationships, which go beyond a vertical transmission of knowledge, call for approaches inspired by the theories of care. What is the meaning of these relationships based on women's care from the point of view of sociality and in relation to the institution of sport? This is the main question that will be addressed here. Approaches of care emphasize accompaniment, maintenance, and the "ethics of love" (Molinier, 2013). They seem to be a good way to identify the contours of a “sports maternalism” which makes such a commitment valid while at the same time conferring legitimacy on a sports practice that is poorly considered.